P1006IMPACT OF GLUCOSE-LOWERING AND ANTIHYPERTENSIVE MEDICATIONS ON DEVELOPMENT OF MICROALBUMINURIA IN SUBJECTS WITH TYPE 2 DIATETES AND NORMOALBUMINURIA IN THE PRIORITY STUDY. (6th June 2020) - Tofte, Nete; Lindhardt, Morten; Currie, Gemma; Frimodt-Moeller, Marie; Von der Leyen, Heiko; Delles, Christian; Mischak, Harald; Rossing, Peter; For the PRIORITY Investigators,
Abstract: Background and Aims: In the PRIORITY study, it was recently demonstrated that the urinary peptidome-based classifier CKD273 was associated with increased risk for progression to microalbuminuria. In this sub-study, we aim to evaluate whether glucose-lowering and antihypertensive medications, many of which have been demonstrated to have albuminuria-lowering effects, may interfere with the predictive value of CKD273. Method: A post hoc analysis of a prospective observational study with embedded randomised placebo-controlled trial. Setting: 1775 subjects from 15 European sites with a mean follow-up time of 2.6 years (minimum of 7 days and a maximum of 4.3 years). Patients: Subjects with T2D, normoalbuminuria and estimated glomerular filtration rate (eGFR) ≥ 45 ml/min/1.73m 2 . Participants were stratified into high- or low-risk groups based on their CKD273 score in a urine sample at screening (high-risk defined as score > 0.154). Main outcome measures: Baseline medication or initiation during the study was assessed for the following medications: glitazones, glucagon-like peptide-1 receptor agonists (GLP1-RA), sodium-glucose cotransporter-2 inhibitors (SGLT2i), dipeptidyl peptidase-4 inhibitors (DPP4i), angiotensin-converting-enzyme inhibitors (ACEi), angiotensin-II-receptor blockers (ARB), calcium channel blockers (CCB) and beta blockers (BB). The main outcome was development of confirmed microalbuminuria (urinary albumin to creatinine ratio (UACR) >30 mg/g and with ≥30% increase from baseline) in 2 of 3 consecutive samples. Results: The hazard ratio (HR (95% CI)) for development of microalbuminuria (high vs. low-risk) was 3.9 (2.9-5.3) in a crude Cox-model; and 2.4 (1.8-3.4; p<0.0001) when adjusted for age, sex, HbA1c, systolic blood pressure, retinopathy, eGFR and UACR. Adding baseline medications to the model did not significantly alter the results. When evaluating medications initiated during the study, more high- than low-risk subjects were started on glitazones, GLP1-RA, SGLT2i, CCB and BB (p<0.03), however, only initiation of DPP4i was associated with the outcome. Adjustment for DPP4i initiated during the study did not significantly change the HR for development of confirmed microalbuminuria (HR 2.5 (1.8 to 3.4); p<0.0001) in a model including eGFR and UACR. The HR for development of persistent microalbuminuria (spironolactone vs. placebo) was 0.81 (0.49-1.34; p=0.41), however, adjusting for DPP4i did not significantly alter this result. Conclusion: Although several glucose-lowering and antihypertensive medications were more frequently prescribed in high-risk subjects, the CKD273 classifier prospectively predicted confirmed microalbuminuria, independent of baseline co-medications and medication initiated during the study. Moreover, initiated medications during the study could not explain the inability of spironolactone to delay progression to microalbuminuria.